1996
DOI: 10.2118/29784-pa
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corrosion on the Oil and Gas Industry

Abstract: Summary The impact of corrosion on the oil industry has been viewed in terms of its effect on both capital and operational expenditures (CAPEX and OPEX) and health, safety and the environment (HSE). To fight against the high cost and the impact of corrosion within the oil industry, an overview of topical research and engineering activities is presented. This covers corrosion and metallurgy issues related to drilling, production, transportation and refinery activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(98 citation statements)
references
References 3 publications
0
94
0
4
Order By: Relevance
“…At temperatures above 80°C the destruction of the metal hydrogen [7] significantly decreases the transition temperature range (65°C -80°C) fractures rarely occur, and the real danger of destruction of metal hydrogen begins just below 65°C.…”
Section: Hydrogen Sulfide Effect (H 2 S)mentioning
confidence: 99%
“…At temperatures above 80°C the destruction of the metal hydrogen [7] significantly decreases the transition temperature range (65°C -80°C) fractures rarely occur, and the real danger of destruction of metal hydrogen begins just below 65°C.…”
Section: Hydrogen Sulfide Effect (H 2 S)mentioning
confidence: 99%
“…The main concern is the failure of equipment caused by CO2 corrosion, particularly the main downhole tubing and transmission pipelines, which results in disruption of the oil and gas production. Failures related to corrosion comprise over 25% of failures experienced in this industry, where 28% of it is CO2 related [3]. The costs associated with corrosion cannot be eliminated entirely and it is almost impossible to completely prevent corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms that is present in oil and natural gas fields cause a number of problems that lead to significant costs for the oil and natural gas industries [1,2]. Studies have shown that microorganisms can significantly alter or degrade a number of hydrocarbons in both oil and natural gas [3,4].…”
mentioning
confidence: 99%
“…Studies have shown that microorganisms can significantly alter or degrade a number of hydrocarbons in both oil and natural gas [3,4]. Numerous studies have also shown that sulfide production by microorganisms in oil and natural gas fields can lead to a number of problems, including reservoir plugging, reservoir souring, reduced product quality, and corrosion of metal-containing equipment [1,2,5,6]. Even though it is clear that microorganisms cause problems in oil and natural gas fields, very little is known about the origin of microorganisms in these ecosystems [7].…”
mentioning
confidence: 99%